Potencial biológico dos extratos obtidos da folha do cumaru (Amburana cearensis A.C. Smith) sobre bactérias transmitidas por alimentos - Lima, Carolline de Brito (2018)
Plants produce from their secondary metabolism bioactive compounds that have antimicrobial property. Thus, there is a growing interest in the food industry in using plant extracts as natural antimicrobials instead of synthetic ones. The increase in consumer interest in more natural products, the carcinogenic and teratogenic character attributed to synthetic preservatives and the growth of microbial resistance to traditional preservatives, has justified this substitution. Thus, this work had as objective to evaluate the antimicrobial activity of crude and microencapsulated extracts obtained from the leaf of cumaru against bacteria transmitted in food. Three extracts were prepared from the coumaru leaf, the aqueous extract (EA) by the decoction method and the hydroalcoholic extracts 50:50 (EHA 50:50) and hydroalcoholic 70:30 (EHA 70:30) by the maceration method. The extracts were characterized as extraction yield, determination of total phenolic compounds, total antioxidants and toxicity. The antimicrobial activity of the extracts was determined against Gram positive (Listeria monocytogenes and Staphylococcus aureus) and Gram negative (Escherichia coli and Salmonella enteritidis) microorganisms. The hydroalcoholic extracts presented better yield of extraction. The EHA 50:50 differed from the others presenting higher content of phenolic compounds and none of the extracts differed as to the total antioxidants. None of the extracts presented toxic effects. All the extracts presented antimicrobial activity against the studied microorganisms, being the Gram positive bacteria more sensitive. The EA had a lower CIM compared to S. aureus and the lowest 50:50 EHA CBM for this microorganism. The hydroalcoholic extracts showed better antimicrobial activity for the other microorganisms tested. As the CIM and CBM found in the antimicrobial activity of the hydroalcoholic extracts against the studied microorganisms were similar, it was decided to continue the studies with a hydroalcoholic extract. The EHA 50:50 was chosen because it presents higher content of total phenolic compounds and requires a lower concentration of alcohol in the extraction process. The effect of EA and EHA 50:50 was evaluated on the morphology of bacterial cells by Electron Transmission Electron Microscopy and sharp changes were observed in bacterial morphology when in contact with the bactericidal concentrations of these extracts. EA and 50:50 EHA were encapsulated using maltodextrin, -cyclodextrin and the combination of these two (1: 1) as the wall material by the freeze-drying method. Microcapsules were characterized for encapsulation efficiency, particle size, zeta potential, morphology, hygroscopicity, colorimetry and antimicrobial activity. The microcapsules of both extracts presented efficient encapsulation of the phenolic compounds. Microcapsules obtained with the -cyclodextrin and maltodextrin mixtures showed larger particle size. The zeta potential of all microcapsules presented negative value and moderate stability. Microcapsules obtained by lyophilization presented irregular morphology. Those that used -cyclodextrin as a wall material were more hygroscopic. The microcapsules of the 50:50 hydroalcoholic extract presented better antimicrobial activity than the microcapsules of the aqueous extract of cumaru. The results obtained suggest that the extracts of the cumaru leaf can be an alternative of antimicrobial agent to be used in the food industry as a substitute for synthetic preservatives.